Optimalisasi Manajemen Waktu Peserta Didik untuk Meningkatkan Produktivitas Belajar - Ristianingsih (Jurnal Psikoedukasia, 2024)
This research investigates the impact of optimizing time management on students' learning productivity. The focus of this research is to analyze efficient time allocation strategies to increase students' awareness of the use of their time. The literature review method was used to develop a conceptual framework and evaluate findings related to time management, effective learning, and learning productivity. The research results show that implementing time management optimization strategies is significantly correlated with increasing learning productivity. Students who are able to manage their time well show increased focus, motivation and quality of work, which is reflected in the results of academic evaluations and assessments. Supporting factors such as family support, self-awareness, and involvement in extracurricular activities were also identified as important contributors in forming good time management habits. In addition, the role of teachers and parents has proven crucial in helping students optimize their time management through close collaboration, creating a supportive educational environment, and facilitating effective learning. These results have practical implications for the development of educational approaches that strengthen students' time management skills. By providing a theoretical foundation and empirical evidence, this research provides valuable insights for educational institutions, teachers, parents, and students to increase learning productivity through effective time management practices. These findings also provide a basis for further research to further explore time management optimization strategies that can be applied in diverse educational contexts. Keywords: Time Management, Students, Learning Productivity.